Schaum's outlines : probability, random variables, and random processes - Hsu, Hwei P. (Hwei Piao), 1930- (USA : McGraw Hill Education, 2020)
Variables, Introduction to Probability and Statistics courses. PLUS: Access to the revised Schaums.com website and new app, containing 23 problem-solving videos, and more. Schaum's reinforces the main concepts required in your course and offers hundreds of practice exercises to help you succeed. Use Schaum's to shorten your study time- and get your best test scores! Schaum's Outlines-- Problem solved.
Includes index.
Keywords: Probabilities -- Outlines, syllabi, etc; Probabilities -- Problems, exercises, etc; Stochastic processes -- Outlines, syllabi, etc; Stochastic processes -- Problems, exercises, etc; Random variables -- Outlines, syllabi, etc; Random variables -- Problems, exercises, etc